Case of Fatal Meningoencephalitis following Accidental Near Drowning - Vykuntaraju K Gowda; Chetan Kerur; Alkarani Patil; Sanjay K Shivappa (Pediatric Infectious Disease)
Introduction: Central Nervous System infections are the most common cause of mortality and morbidity in developing countries. We are reporting a rare case of neuroinfection following drowning. Case description: Fourteen-year-old boy with a history of near drowning was initially treated for respiratory distress requiring mechanical ventilation and a right femur fracture. He was all right for 15 days at home later he developed a fever and weakness in his left lower and upper limbs. MRI of the brain showed a mass lesion with vasogenic edema requiring decompression craniotomy. Brain biopsy during decompressive craniectomy showed granulomatous inflammation composed of sheets of histiocytes, lymphocytes, and many foreign body giant cells. PAS and GMS stains highlight fungal hyphae/pseudohyphae. Conclusion: Fungal meningoencephalitis should be considered in case of neuro infection following near drowning in addition to bacterial infections and should be treated urgently.